Development and validation of IYCF-CCPQ to assess knowledge, attitude and practice (KAP) on infant and young child feeding and factors associated with the kap scores among child care providers in Kelantan - Zakria, Najihah Mahfuzah (2019)
Adequate nutrition is critical to child health. There is a need to identify the knowledge, attitude, and practice (KAP) on infant and young child feeding among child care providers. Pre-existing questionnaires are unsatisfactory due to a different target population, weak theory, and lack of confirmatory analysis. Our objectives were t o develop and validate a new questionnaire that will be use d to assess the KAP and its associated factors among child care provider s in Kota Bharu. This study consists of two phases which Phase 1 developed and validate a new questionnaire, meanwhile Phase 2 involved assessment of KAP and its associated factors. The questionnaire was developed based on literature review, experts’ opinion and theoretical framework. Response process was assessed via cognitive debriefing and pretesting. Psychometric validation was carried out among 200 child care providers outside Kota Bharu. Purposive sampling was applied. Item Response Theory and Exploratory Factor Analysis were used for internal structure validity . Internal consistency rel iability was conducted for all domains. For Phase 2, a cross-sectional study involved 150 child care providers in Kota Bharu. Multistage random sampling was applied. Level of KAP was determined and its associated factors were identified through multiple linear regression and chi-square analysis. As a result, the new questionnaire consists of 218 final items with 3 domains (99 items on knowledge, 77 items on attitude, and 42 items on practice) and named as ‘Borang Kaji Selidik Pemakanan Bayi dan Kanak-Kanak dalam kalangan Pengasuh’ or IYCF-CCPQ. IYCF-CCPQ had good psychometric properties. Internal consistency by marginal reliability ranging from 0.74 to 0.91 for domain knowledge. Reliability for domain attitude ranging from 0.89 to 0.90. Breastfeeding and formula feeding knowledge score (BFFKS) was 69.42 (SD 11.31), complementary feeding knowledge score (CFKS) was 76.99 (SD 9.31), breastfeeding and formula feeding attitude score (BFFAS) was 143.61 (SD 12.10); and complementary feeding attitude score (CFAS) was 176.69 (16.07). Exclusive breastfeeding experience (adjusted b=7.09; 95%CI 1.69,12.48; p=0.001) and number provider per centre (adjusted b=-0.41; 95%CI -0.77,-0.06; p=0.022) did had association with BFFKS. Being married had significant association with BFFKS (adjusted b=6.01; 95%CI 2.32,9.71; p<0.001), BFFAS (adjusted b=5.33; 95%CI 1.40,9.26; p=0.008) and CFAS (adjusted b=7.69; 95%CI 2.94,12.45; p=0.002). Increased total working hours per day (adjusted b=2.53; 95%CI 1.06,4.00; p<0.001) did have association with CFKS. Diploma or higher qualification did influence CFKS (adjusted b=3.13; 95%CI 0.08,6.19; p=0.046), BFFAS (adjusted b=5.33; 95%CI 21.40,9.26; p=0.008) and CFAS (adjusted b=10.74; 95%CI 5.69,15.79; p<0.001). Job scope less than five did influence CFKS (adjusted b=4.67; 95%CI 1.79,7.54; p=0.001), BFAS (adjusted b=3.94; 95%CI 0.29,7.58; p=0.036) and CFAS (adjusted b=8.24; 95%CI 3.53,12.94; p<0.001). Source information from health staff did influence CFKS (adjusted b=3.16; 95%CI 0.05,6.27; p=0.048). Meanwhile, pamphlet source had association with CFAS (adjusted b=5.89; 95%CI 0.79,11.00; p=0.025). There was a significant association of educational level (X2=8.12(3),p=0.044) and exclusive breastfeeding (p=0.041, fisher exact test) with the practice of handling express breastmilk. Meanwhile, hygenic practice did have association with educational level (p=0.048, fisher exact test). In conclusion, the IYCF-CCPQ is reliable and valid to be used to assess KAP among child care providers on infant young child feeding. Overall KAP was satisfactory and identified significant factors help in improving child care providers’ KAP in future.